Requiring help injecting among people who inject drugs in Toronto, Canada: Characterising the need to address sociodemographic disparities and substance‐use specific patterns. (16th May 2022) - Mitra, Sanjana; Kolla, Gillian; Bardwell, Geoff; Wang, Rick; Sniderman, Ruby; Mason, Kate; Werb, Dan; Scheim, Ayden
Abstract: Introduction: Those requiring help injecting are at an elevated risk of injection‐related injury and blood‐borne infections and are thus a priority group for harm reduction programs. As supervised consumption services (SCS) are scaled‐up across Canada, information on those who require help injecting is necessary to inform equitable service uptake. We characterised the sociodemographic, structural and drug use correlates of needing help injecting among a cohort of people who inject drugs in Toronto, Canada. Methods: A cross‐sectional baseline survey was administered between November 2018 and March 2020. Unadjusted and multivariable logistic regression models examined associations with requiring help injecting in the past 6 months. A gender‐stratified sub‐analysis described characteristics of receiving help among those requiring it. Results: Of 701 participants (31.0% cisgender women), 294 (41.9%) needed recent help injecting. In unadjusted analyses, being a racialised, non‐Indigenous person (odds ratio [OR] 1.79, 95% confidence interval [CI] 1.13–2.86) or a cisgender woman (OR 1.72, 95% CI 1.24–2.39) were associated with needing help. In multivariable analyses, requiring assistance was associated with needing frequent help preparing drugs (adjusted OR [AOR] 9.52, 95% CI 4.78–21.28), fewer years since first injection (AOR for 1 year increase: 0.97, 95% CI 0.95–0.99) and injecting stimulants. Among those who required help, cisgender women reported needing assistance more often than cisgender men ( P  = 0.009). Discussion and Conclusions: Over two‐fifths of the sample required help injecting; requiring assistance was associated with sociodemographic indicators and substance use‐specific patterns. Findings highlight the need to scale‐up educational resources for those who receive or provide help injecting, as well as SCS that accommodate onsite injection assistance.